PERILAKU KEPEMIMPINAN BERORIENTASI HUBUNGAN SEBAGAI ANTESEDEN, SELFEFFICACY DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Pieter Sahertian (Jurnal Keuangan dan Perbankan, 2008)
This study was aimed at analyzing the influence of the worker perception about theleadership behavior which had relationship-oriented from the leader or the supervisor towardsthe work through self-efficacy and organizational citizenship behavior. To gain the objectives,explanatory research was conducted in correlational research. The samples were made of 125respondents from the workers of PT. Bank Central Asia Tbk. District VII Malang who had thepositions from supervisors (SPV) till chief managers (CM) with simple sampling technique. Thedata were taken from questionnaire and interview as the instruments of the research. Then,they were analyzed by using Structural Equation Modelling (SEM) as the statistical techniquewith rate a = 0,05. The results of the research showed: 1) the tendency of the leaders of PT BCATbk. District VII Malang in applying leadership behaviour with relationship-oriented was high,and so were the self-efficacy, and extra-role (OCB) workship (either the employee or theemployer). 2) The influence of leadership behaviour with relationship-oriented towards extrarole (OCB) workship was not significant. The correlations among those variables changed afterthey were interfered by self-efficacy variable as the moderator variable. 3) The result of thisresearch showed that self-efficacy variable mediated the influence of leadership behaviourwith relationship-oriented towards extra-role workship (OCB).